Diseño de un manual para la implementación de nómina electrónica en Distripartes moreno (2021)
The research that is developed below has the purpose of analyzing, verifying the importance, the regulations and the requirements that must be taken into account for the acceptance of the DIAN in the supporting document of the electronic payroll and its adjustment note in Colombian companies. . In addition, the importance and generalities that a procedures manual must contain will be observed, which will be designed step by step for the implementation of payroll in the Distripartes Moreno SAS company in the city of Duitama. In companies, the importance of having control over the activities that are carried out is reflected, as well as staying in constant innovation with tax issues, because the systems constantly have many updates and it is necessary to learn these new implementation issues. Train the staff who will develop and implement the new activities, as well as the person who will be in charge of carefully reviewing these processes to see if they meet the established requirements.